J22 Chronobiological approaches and habitual routine: effect on morning physical performance in male team sport players - Middleton, Harvey; Fernley, Jack; Chadwick, Michael; Brownrigg, Ellie; Calcagni, Eddie; Snowe, Hayden; Blow, Liv; Porritt, George; Durkin, Kyle; Edwards, Ben (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Achieving peak morning physical performance for team sport players is vital due to the vast degree of performances tend to take place in the morning. It has been well-documented that undertaking chronobiological approaches and having a habitual routine can have an impact on performance, however the combination of the two have not been clearly interpreted. Therefore, the aim of the present study was to examine how combined chronobiological approaches and habitual routine had an influence on morning physical performance. Using a double-blinded, randomized counterbalanced design, team sport male participants (n = 12) were recruited, with institutional ethics approval, and completed five sessions: (i) two familiarization sessions; (ii) one bright light (BL) morning exercise condition; (iii) two testing conditions either: habitual (the morning after BL), or No pill. The morning physical performance tests carried out were as followed: Intra-aural temperature and fingertip blood glucose and lactate, taken throughout: at rest, post warm-up and immediately after the RSP test, mood assessed using Perceived Onset Mood State (POMS) questionnaire, 3 right and 3 left hand grip strength measures, and a maximal repeated sprint performance (RSP) protocol (10 × 20 m, 30 s recovery period). Heart rate (HR), thermal comfort (TC), and rating of perceived exertion (RPE) were all recorded after each sprint. Data were analysed using a general-linear model.